2013
DOI: 10.1155/2013/936063
|View full text |Cite
|
Sign up to set email alerts
|

Immune Response following Liver Transplantation Compared to Kidney Transplantation: Usefulness of Monitoring Peripheral Blood CD4+ Adenosine Triphosphate Activity and Cytochrome P450 3A5 Genotype Assay

Abstract: Seventy living donor liver transplantation (LDLT) and 39 kidney transplantation (KT) patients were randomly screened by using the peripheral blood CD4+ adenosine triphosphate activity (ATP) assay (IMK assay). The patients were divided into 2 groups in each organ transplantation with low IMK ATP level (<225 ng/mL) or high (>225) (LT-L: n = 23, KT-L: n = 19, LT-H: n = 47, and KT-H: n = 20, resp.). The incidence of bacterial and/or viral infection was significantly higher in LT-L group than in LT-H group (74.0 ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…in 2002, monitors the function of cluster of differentiation (CD) 4 + T cells by measuring the intracellular concentration of adenosine triphosphate (ATP) (8). The IMK assay has previously been used to identify transplant patients at risk of infection (patients with low IMK ATP levels: <225 ng/ml) or rejection (patients with high IMK ATP (1,2,9). However, it has been argued that the IMK assay is not a useful indicator of infection or rejection risk (3,4), and for patients with autoimmune diseases, the efficacy of the IMK assay in monitoring immunological aspects remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…in 2002, monitors the function of cluster of differentiation (CD) 4 + T cells by measuring the intracellular concentration of adenosine triphosphate (ATP) (8). The IMK assay has previously been used to identify transplant patients at risk of infection (patients with low IMK ATP levels: <225 ng/ml) or rejection (patients with high IMK ATP (1,2,9). However, it has been argued that the IMK assay is not a useful indicator of infection or rejection risk (3,4), and for patients with autoimmune diseases, the efficacy of the IMK assay in monitoring immunological aspects remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…It is well established that the CYP3A5 genotype is associated with variability in blood tacrolimus concentrations, and the authors have also reported correlations between genetic polymorphisms and blood tacrolimus levels in individuals who have undergone kidney, liver, or hematopoietic stem cell transplantation. [24][25][26] The patient who experienced acute rejection was found to have the CYP3A5 1/*3 genotype, which is not generally associated with markedly elevated blood tacrolimus levels. However, there were no appreciable changes in the AUC of mycophenolic acid, inhibition of the IL-2 receptor by basiliximab in CD4 + T cells, or the expression levels of IL-2 and IFN-γ in effector T cells.…”
Section: Discussionmentioning
confidence: 99%
“…However, these studies measured the ImmuKnow values at the time of disease rather than before its onset, which prevented any analysis on the predictive value of the assay. Other investigators tried to address this issue and reported that low ImmuKnow values are associated with an increased incidence of infections in stable transplant recipients on maintenance immunosuppression [89, 9295]. Yet, these studies were small with relatively few infection episodes and short follow-up periods.…”
Section: Immuknowmentioning
confidence: 99%